Strapdown inertial navigation technology - Titterton, D. H. (Institution of Electrical Engineers, 2004)
"This book sets out to provide a clear and concise description of the physical principles of inertial navigation, the associated growth of errors and their compensation. There is also detailed treatment of recent developments in inertial sensor technology and a description of techniques for implementing and evaluating such systems. This new edition includes a number of refinements covering sensor technology, geodesy and error modelling, plus new chapters on MEMS technology and inertial systems applications."--Jacket
Co-published by the American Institute of Aeronautics and Astronautics.
Previous edition: London: Peter Peregrinus, 1997.
Keywords: Inertial navigation (Aeronautics); Inertial navigation systems.; elektronické knihy; electronic books